The Perspective of Peace or Fear for the Future? An Attempt to Evaluate Christian-Muslim Dialogue - Piotr Kaczmarek (Warszawskie Studia Teologiczne)
The paper indicates the diagnosis the Christian-Muslim dialogue conducted by the Catholic Church, especially taking into account the indications of the Second Vatican Council. The question arises whether the mutual discourse of the representatives of the two religions is currently giving rise to a perspective of peace, or rather fear for the future? There is no denying that militant Islam accentuates the escalation of violence. These behaviors can give rise to fear and questions about the possibility of coexistence in this world. These events build up the circumstances of our time, which theology must to explain. To examine the wider context, the teaching of Vatican II on dialogue with Islam was recalled, and the teaching and actions of the post-Conciliar popes were recalled. This effort clearly indicated the possibility of cooperation, but also delineated the limits, which the Church must not cross. Therefore, although there is a real opportunity to develop joint projects, there are also significant limitations. Moreover, as practice shows, the Church's benevolent gestures often fall on deaf ears, and it seems that this effort is inadequate to the expected fruits of dialogue. Therefore, the possibility of dialogue can be discovered in Catholic Mariology. The person of Mary can become the reason for Muslims to turn to Christianity, which is shown by certain indications of the piety of the followers of Islam towards Mary. It is also an important premise for the Church to rely less on human action and strategy lined with diplomacy and politics. It is necessary to pray much more for the conversion of Muslims, so that God Himself may do the work of changing the hearts of the followers of Islam.